Penyusunan Butir Soal Unsur Bahasa Arab (Bunyi, Kosakata, dan Struktur Kalimat) dan Uji Instrumen Butir Soal di MTs S Aluppang - Fitra, Muh. Naufal; Chamidah, Dewi; Basit, Sitti Najmianti Rahma; Sardiyanah, Sardiyanah (Universitas Islam Ahmad Dahlan Sinjai, 2024)
The question items that have been prepared so far are more invalid than valid and the level of difficulty and form of the test given still does not vary. In addition, there are still many questions given to students that have not been tested for validity and reliability. This study aims to compile questions on Arabic language elements (sounds, vocabulary, and sentence structure) and test the question instruments in MTs S Aluppang. This research is expected to produce valid and reliable question items so that it can be used to measure the level of mastery of Arabic elements of the students of MTs S Aluppang more accurately and objectively. This study uses a quantitative approach. The preparation of question items in this study is carried out based on the stages of assessment planning according to Munip (2017). The test instrument trial was carried out for students of class VIII MTs S Aluppang totaling 13 students. The study results showed that the preparation of question items had gone through the appropriate stages and produced 10 questions for each aspect of language elements. In general, the test of the question item instrument showed that there were 16 question items, or 53% of the total question items that were suitable for reuse and there were 14 question items, or 47% of the total question items that had to be corrected or discarded.